Escape Classroom or How to Transform the Foreign Language Classroom into a Mysterious Learning Space - Irina Mishkova-Yotova (Педагогически форум)
The methodology of educational puzzle rooms is used to increase competences by creating a motivating and engaging learning experience. The Educational Puzzle Room game is characterized by a specific focus on learning objectives that are woven into the overall design, concept, content and experience. The set goals can be both for building and also for demonstrating certain key competences and skills: creation and teamwork skills, communication skills, time management skills, critical and creative thinking skills. In foreign language education (FLET), educational riddle rooms are applied, mainly assigning linguistic riddles related to the manifestation of observation, combinability, resourcefulness, orientation in space, teamwork. At the same time, through them, learning becomes exciting and fun, and the process is social and connects learning content with real life. The article presents the mainstages of organization in the transformation of the classroom into an educational room of riddles and its implementation in a lesson in a foreign language – English.